Revisiting Subspecialty Training in Cardiology in Indonesia: Structural, Regulatory, and Global Perspectives - Munawar, Muhammad; Lubis, Anggia Chairuddin; Setianto, Budi Yuli; Octaviono, Yudi Her; Munawar, Andina; Rifqi, Sodiqur; Widito, Sasmojo (The Indonesian Heart Association, 2025)
The rapid expansion of cardiology as a discipline has prompted the emergence of numerous subspecialties that require structured, competency-based training. In Indonesia, however, the development of subspecialty education remains inconsistent, divided between university-based programs known as Spesialis-2 (Sp-2) and hospital-based fellowships. The interchangeable use of the terms “fellowship” and “subspecialty” has generated conceptual ambiguity and regulatory uncertainty. Globally, subspecialty training in cardiology follows a hospital-based apprenticeship model, led by accredited teaching hospitals and closely regulated by professional boards such as ACGME, ACC, or ESC. Indonesia’s deviation from these international norms has implications not only for the quality of advanced cardiovascular training but also for the nation’s ability to attract international fellows—a marker of global academic recognition. This review examines the current landscape of cardiology subspecialty education in Indonesia, contrasting it with global frameworks, and discusses structural, academic, and legal challenges, including those concerning foreign trainees. The article concludes by proposing a policy framework to harmonize Indonesia’s subspecialty education with global standards, thereby strengthening both national capacity and international credibility.